ARUS KAS, LABA AKUNTANSI, KARAKTERISTIK KORPORAT, DAN RETURN SAHAM PADA PERUSAHAAN SEKTOR BASIC MATERIAL - Valentino, Gland William; Surianti, Surianti; Destriani, Mutiara; Dosinta, Nina Febriana; Rusmita, Sari (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study aims to determine the effect of cash flow, accounting earnings, firm size, and financing decisions on stock returns. The population in this study was basic material sector companies listed on the Indonesia Stock Exchange in the 2018-2021 periods. The sampling technique used a purposive sampling method with predetermined criteria and obtained a sample of 34 companies with 135 observations. The data of the companies' financial statements are obtained from the official website of IDX. This study analyzes panel data regression using the Random Effect Model with the help of Eviews 12 application. Furthermore, the results show that cash flow from operations, cash flow from investments, cash flow from funding, firm size, and financing decisions do not affect stock returns while accounting earnings positively affect stock returns. The results of this study indicate that investors capture the positive signals that the company has given through accounting earnings.